2014
DOI: 10.1007/s00441-014-2074-7
|View full text |Cite
|
Sign up to set email alerts
|

Listening to another sense: somatosensory integration in the auditory system

Abstract: Conventionally, sensory systems are viewed as separate entities, each with its own physiological process serving a different purpose. However, many functions require integrative inputs from multiple sensory systems, and sensory intersection and convergence occur throughout the central nervous system. The neural processes for hearing perception undergo significant modulation by the two other major sensory systems, vision and somatosensation. This synthesis occurs at every level of the ascending auditory pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 173 publications
(208 reference statements)
1
45
0
6
Order By: Relevance
“…The literature suggests that the neural signals from the auditory pathway are significantly modulated by the visual system and the somatosensory system. Additional investigations showed that this modulation occurs at a minimum of three different locations in the ascending auditory pathway: Inferior colliculus, Medial Geniculate Body and Auditory Cortex [45]. A hallmark investigation concurring with past research showed that Cross-modal mapping of low luminescence to low pitch sounds and high luminescence to high pitch sounds may have evolved before humans.…”
Section: Kiki-bouba and Biologysupporting
confidence: 65%
“…The literature suggests that the neural signals from the auditory pathway are significantly modulated by the visual system and the somatosensory system. Additional investigations showed that this modulation occurs at a minimum of three different locations in the ascending auditory pathway: Inferior colliculus, Medial Geniculate Body and Auditory Cortex [45]. A hallmark investigation concurring with past research showed that Cross-modal mapping of low luminescence to low pitch sounds and high luminescence to high pitch sounds may have evolved before humans.…”
Section: Kiki-bouba and Biologysupporting
confidence: 65%
“…Integration of auditory and somatosensory afferent projections occurs in peripheral brain structures as early as the CN, where projections from the AN and trigeminal and dorsal column ganglia and brain stem nuclei converge [95, 96]. These projection neurons terminate primarily on the CN granule cells, whose parallel-fiber axons terminate on the apical dendrites of DCN fusiform cells [9799].…”
Section: Role Of Non-auditory Structuresmentioning
confidence: 99%
“…This type of tinnitus derives from complex somatosensory-auditory interactions and cross-modal mechanisms that mainly arise from musculoskeletal anatomical regions such as the temporomandibular joint (TMJ), craniocervical junction, cervical vertebrae, and neck and shoulder muscles (NECK) [Chan and Reade, 1994;Levine et al, 2003;Abel and Levine, 2004;Tullberg and Ernberg, 2006;Björne, 2007;Bernhardt et al, 2011;Vielsmeier et al, 2012;Buergers et al, 2014]. Animal studies have shown that projections from the auditory nerve and trigeminal and dorsal column ganglia and brainstem nuclei integrate in the cochlear dorsal nucleus [Haenggeli et al, 2005;Zhan et al, 2006;Dehmel et al, 2008;Wu et al, 2014]; furthermore, nonacoustic stimulation can modulate both the firing rates and temporal response patterns to the acoustic stimulation in the inferior colliculus, which receives inputs from the dorsal cochlear nucleus and the somatosensory nuclei [Zhou and Shore, 2006].…”
Section: Introductionmentioning
confidence: 99%